The Effect of N-Acetylcysteine on Glomerulus Filtration Rate in Patients with Chronic Kidney Disease Post Percutaneous Coronary Intervention - Putu Rika Veryanti; Gamaliel Agripa; Ketut Agus Adrianta (Universitas Padjadjaran, 2022)
The use of contrast for percutaneous coronary intervention (PCI) procedures in chronic kidney disease (CKD) patients can worsen kidney function. N-Acetylcysteine is widely used as a preventive therapy for contrast-induced nephropathy (CIN). However, previous studies have shown inconsistent results, so that further research regarding the effectiveness of N-Acetylcysteine to prevent CIN is needed. This study aimed to determine the effect of N-Acetylcysteine on glomerulus filtration rate (GFR) in patients with CKD who underwent PCI. This research was conducted at Jakarta's national central general hospitals from July to December 2019 with a retrospective study design. Through the purposive sampling method, we obtained 72 samples. The sample was selected from the patient's medical records in the period January-June 2019. Patients who underwent PCI and had a history of CKD were included in the study. The data were analyzed by t and chi-square tests to determine the effect of N-Acetylcysteine on the patient's GFR. The results showed that CKD patients underwent PCI were dominated by male (61.11% vs 38.89%) and 33.33% of patients aged 55-64 years. Most patients had GFR values between 30-59.99 ml/min/1.73m2 with 100 ml of contrast administration. The ratio of contrast amount to GFR > 3.7 was found in 47.22% of patients. The administration of N-Acetylcysteine as a preventive therapy for CIN post-PCI increased the GFR value of CKD patients by 2.69±5.72. N-Acetylcysteine had a significant effect on the GFR of post-PCI CKD patients (p=0.000).